Implementation of Content Differentiation in Early Childhood Education Learning at Medan City Sekolah Penggerak - Siti Khodijah Lubis; Wan Nova Listia; Dwi Septi Anjas Wulan; Elya Siska Anggraini; Sariana Marbun (SOSIOEDUKASI, 2025)
This research aims to investigate the implementation of content differentiation in early childhood education at Medan City Medan Sekolah Penggerak. The method employed is qualitative research, utilizing purposive sampling. Interviews, observations, and documentation were conducted as data collection techniques. Data analysis techniques include data collection, data reduction, data presentation, conclusion drawing, and verification, while for data validity, source triangulation is used. The results showed that PAUD units in Medan City Sekolah Penggerak have implemented content differentiation by adjusting teaching materials based on children's readiness, interests, and learning styles. Teachers utilize various learning media and technology and provide space for children's active participation. Challenges faced by teachers include limited time, children's abilities, facilities, and teachers' skills in creating varied materials. Training, improved facilities, and collaboration between teachers are needed to optimize the implementation of content differentiation.